2021
DOI: 10.1177/0022057421996256
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Relationship Between Schools’ DNA Profiles and Organizational Happiness According to the Perception of Teachers

Abstract: This research was carried out with the aim of determining the relationship between schools’ DNA profiles and organizational happiness according to teachers’ perceptions. The research sample consists of 404 teachers who work at primary or secondary public schools in Rize, Turkey. The research model is a correlational survey model. As a result of the research, the resilient organizations have the highest perception level among the school DNA profiles according to the perceptions of teachers. In addition, it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Sharma's (2012) study concluded that male teachers are happier than female teachers. On the other side, the study, carried out by Köse (2020) with teachers working at primary and high schools, determined that female teachers had higher levels of organizational happiness than male teachers. When the results are assessed together, it can be said that the organizational happiness is not clear in terms of gender.…”
Section: Discussion Results and Recommendationsmentioning
confidence: 99%
“…Similarly, Sharma's (2012) study concluded that male teachers are happier than female teachers. On the other side, the study, carried out by Köse (2020) with teachers working at primary and high schools, determined that female teachers had higher levels of organizational happiness than male teachers. When the results are assessed together, it can be said that the organizational happiness is not clear in terms of gender.…”
Section: Discussion Results and Recommendationsmentioning
confidence: 99%